Effect of Product Quality and Service Quality Customer Satisfaction of Yoghurt Milk Products - Safitri, Dewi; Sukmawati, Dety; Nataliningsih, Nataliningsih (Journal of Sustainable Agribusiness, 2024)
The purpose of this study was to determine the effect of product quality and service quality on customer satisfaction of yogurt milk products. The unit of analysis is the students of Pacet 1 State Vocational School, Pacet District, Cianjur Regency. Respondent identification technique was carried out by simple random sampling and 115 respondents were identified. The analysis technique used is path analysis. With the results obtained Product Quality Performance which includes dimensions: product aesthetics; Product benefits (yogurt milk); Durability and price suitability reach good criteria in Cianjur City at 81.40%. Diversity of service quality, including dimensions / attributes of direct evidence and reliability; responsive; and Yoghurt Milk Guarantee in Cianjur City reached 79.33% good criterion. Customer satisfaction, which includes the following dimensions: product quality; price factor; The cost factor and the availability of yogurt milk in Cianjur City reached a good criterion of 77.44%. There is a positive relationship between product quality and service quality of yogurt milk as indicated by the correlation coefficient r = 0.937. That is, the better the quality of market products applied, the better the quality level. Product quality and service quality clearly have a positive effect on yogurt milk customer satisfaction. The proportion of the influence of product quality is 48.72%, which is greater than the effect of service quality, which is 31.24%. The remaining 20.04% is influenced by other factors.